2023
DOI: 10.1002/adma.202303261
|View full text |Cite
|
Sign up to set email alerts
|

Lipid Nanoparticle (LNP) Enables mRNA Delivery for Cancer Therapy

Abstract: Messenger RNA (mRNA) has received great attention in the prevention and treatment of various diseases due to the success of COVID‐19 mRNA vaccines (Comirnaty and Spikevax). To meet the therapeutic purpose, it is required that mRNA must enter the target cells and express sufficient proteins. Therefore, the development of effective delivery systems is necessary and crucial. Lipid nanoparticle (LNP) represents a remarkable vehicle that has indeed accelerated mRNA applications in humans, as several mRNA‐based ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
50
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 118 publications
(50 citation statements)
references
References 216 publications
(366 reference statements)
0
50
0
Order By: Relevance
“…Additionally, LNPs-miRNA-193b exhibited significant delays in leukemia propagation in acute myeloid leukemia xenograft models, while LNPs containing miR-182 impaired tumor growth in triple-negative breast cancer models. , Optimal LNPs should maximize the probability of reaching specific cell types within a target organ and minimize the toxicity and immunogenicity of cargoes . To enhance the stability, transfection efficacy, and safety of LNPs, various optimization strategies such as component selection, surface modification, suitable administration routes, and design of bioinspired compositions and structures have been explored . However, regarding the oral delivery of LNPs, more efforts are required to overcome the challenges presented by the complex digestive tract environment .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, LNPs-miRNA-193b exhibited significant delays in leukemia propagation in acute myeloid leukemia xenograft models, while LNPs containing miR-182 impaired tumor growth in triple-negative breast cancer models. , Optimal LNPs should maximize the probability of reaching specific cell types within a target organ and minimize the toxicity and immunogenicity of cargoes . To enhance the stability, transfection efficacy, and safety of LNPs, various optimization strategies such as component selection, surface modification, suitable administration routes, and design of bioinspired compositions and structures have been explored . However, regarding the oral delivery of LNPs, more efforts are required to overcome the challenges presented by the complex digestive tract environment .…”
Section: Resultsmentioning
confidence: 99%
“…43 To enhance the stability, transfection efficacy, and safety of LNPs, various optimization strategies such as component selection, surface modification, suitable administration routes, and design of bioinspired compositions and structures have been explored. 44 However, regarding the oral delivery of LNPs, more efforts are required to overcome the challenges presented by the complex digestive tract environment. 45 Nonetheless, the restoration of the miR-200 family through a LNPs-based delivery system holds great promise for improving therapeutic efficacy in patients with enteritis or active UC.…”
Section: Delivery Of Mir-200 Via Lipid Nanoparticles Facilitates Inte...mentioning
confidence: 99%
“…The delivery of mRNA is notoriously difficult through simple binding using traditional gene vectors because of the conformation of linear and irregularly elongated mRNA molecules; therefore, efforts have been made to develop ideal mRNA delivery carriers to achieve satisfactory delivery efficiency. 39,40 Indeed, Mai et al reported the use of protamine to concentrate mRNA and encapsulation by DOTAP/Chol/DSPE-PEG cationic liposomes, whereby the cationic liposome/protamine complex exhibited highly effi- 43 Although significant progress has been made in this field, limitations still exist in many aspects, including poor transfection efficiency or the use of "multivector systems" that increase the complexity of mRNA delivery vectors, leading to uncertainty regarding the prepared mRNA formulations. In our study, we demonstrated that the MLSV system can deliver mRNA with high efficiency.…”
Section: ■ Discussionmentioning
confidence: 99%
“…The high efficiency of mRNA delivery is the key point of mRNA-based tumor gene therapy. The delivery of mRNA is notoriously difficult through simple binding using traditional gene vectors because of the conformation of linear and irregularly elongated mRNA molecules; therefore, efforts have been made to develop ideal mRNA delivery carriers to achieve satisfactory delivery efficiency. , Indeed, Mai et al reported the use of protamine to concentrate mRNA and encapsulation by DOTAP/Chol/DSPE-PEG cationic liposomes, whereby the cationic liposome/protamine complex exhibited highly efficient mRNA delivery . Capasso Palmiero et al reported the synthesis of PBAE terpolymers-based diacrylates and dodecyl amine to deliver mRNA with spleen accumulation .…”
Section: Discussionmentioning
confidence: 99%
“…[3] mRNA is an unstable single-stranded macromolecule with a negative charge, a suitable carrier vehicle is crucial for ensuring enhanced target delivery in vivo. [4] The greenlighted mRNA vaccines against COVID-19 which deliver mRNA based on LNP (ALC-0315 LNP or SM102 LNP), Onpattro, is approved by the FDA for the therapy of hereditary transthyretin (TTR)-mediated amyloidosis which is based on DLin-MC3-DMA (MC3) lipid; literature reports have proved that MC3-based LNP can effectively deliver mRNA in vivo. [1,5] However, the mRNA-LNP vaccine has been limited by the safety of administration by repeated or high doses.…”
Section: Introductionmentioning
confidence: 99%